2019
DOI: 10.1108/ijqrm-03-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

A grey-based DEMATEL model for building collaborative resilience in supply chain

Abstract: Purpose The purpose of this paper is to explore the phenomenon of collaborative resilience through in-depth case study research in India. This study endeavours to identify and model the critical success factors of collaborative resilience. Design/methodology/approach Eight critical success factors of collaborative resilience were identified through literature search. Modelling and analysis of these factors was conducted using grey-based DEMATEL method. Data were collected from supply chain experts in Indian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 96 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…A paper by Ref. [ 18 ] analyzed the motivation factors for building resilient supply chains. They concluded that the primary step in building collaborative resilience is to build internal resilience and then focus on the channel partners' efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A paper by Ref. [ 18 ] analyzed the motivation factors for building resilient supply chains. They concluded that the primary step in building collaborative resilience is to build internal resilience and then focus on the channel partners' efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, it is essential to produce a more practical method to evaluate interactions among HCPA under uncertain circumstances systematically. DEMATEL or some form of modified DEMATEL has been successfully used in several recent research works on supply chain management (Aggarwal and Srivastava, 2019; Li et al , 2020; Lin et al , 2018; Ortiz-Barrios et al , 2020). In this research, the author proposes a rough-DEMATEL approach for assessing the interactions among HCPA.…”
Section: Methodsmentioning
confidence: 99%
“…DEMATEL, an MCDM method, is proposed to develop the structural model showing causal relationship among criteria (Malekzadeh et al, 2016;Aggarwal and Srivastava, 2019). This method has been widely used for selection purposes (Singh and Bhanot, 2020).…”
Section: Fuzzy Dematelmentioning
confidence: 99%